Fabrication of Antimicrobial Hydrogel Using Biodegradable Blended Materials for Skin Applications - Abdallah, Lina; Ayyed, Alaa (Al-Nahrain Journal for Engineering Sciences, 2024)
Biodegradable polymers are very useful polymers in biomedical applications. In this research, several hydrogels were fabricated by using two polymers, Polyvinyl alcohol (PVA) and Chitosan (Chs) by the solvent casting method in order to use them for skin applications. Several tests were carried out on these membranes such as Agar diffusion method to examine their antimicrobial activities, Fourier transform infrared microscopy (FTIR) test to study the differences in their chemical structures. Uniaxial tensile test was performed to examine the mechanical characteristics of these membranes. In addition, the wettability test was used to investigate the hydrophobicity or hydrophilicity of the surfaces. The results showed that all membranes are hydrophilic, of which the contact angles are less than 90°. The membrane manufactured from 75:25 Chs-PVA is more hydrophobic (contact angle is 74°) than other membranes made of 50:50 Chs-PVA and 25:75 Chs-PVA as the contact angles were 59° and 61°, respectively. The tensile test results indicate that the membrane fabricated of the PVA and the membrane that was fabricated by 75% Chs and 25% PVA has the highest tensile strength of 17.9 MPa, 16.2 MPa and Young^’ s Modulus of 181.2 MPa and 7.18 MPa, respectively. The highest strain at break was observed by the membrane of 25:75 Chs-PVA which equals to 24.67%. Chitosan membranes showed inhibition zones of about 2.99 cm and 2.75 cm in length, and 75:25 Chs-PVA membranes showed 5.1 and 5.91 cm in length for E.coli. To sum up, this copolymer is considered as promising hydrogel for skin applications such as wound dressing.